Assessment of Some Phosphatic Sources for Possible Accumulation of Heavy Metals in Chilli - Jidesh C V (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 1998)
Rock phosphate sources collected from different locations were analysed for both phosphorus content and heavy metals namely cadmium and lead. Those sources which analysed relatively higher content of heavy metals were included for conducting a pot culture experiment using chilli (Capsicum annuum L.) as test crop. To derive meaningful comparison in the study, partially acidulated rock phosphates as well as direct water soluble source of cadmium and lead were also applied to assess their bioavailability to plants. The influence of organic matter when applied alone or in conjunction with heavy doses of heavy metals was also assessed in the study. The pot culture experiment was conducted in the Vegetable Research Farm, Department of Olericulture, Vellanikkara during the kharif season of 1996, with chilli as the test crop. The entire fertilizer management was based on package of practice (N, P and K at 70, 40 and 25 kg ha-1) recommendation. Five different sources of P selected for the pot culture experiment were (1) Maton rock phosphate, (2) Mussorie rock phosphate, (3) Gafsa rock phosphate, (4) Rajasthan rock phosphate and (5) Single superphosphate. The maximum content of cadmium (55 mg kg-1) was recorded in Gafsa rock followed by 25 mg Cd kg-1 for the Maton rock and single superphosphate analysed the least concentration of cadmium (15 mg kg-1 Highest lead content of 230.5 mg Pb kg-1 was analysed in Maton rock while lowest (38 mg kg-1) in Musoorie rock. All the other sources maintained their heavy metal concentration in between these extremes.